From Words to Lifestyle: Etymology in Popular Language Shaping Social Trends - Firdaus, Fauzan Akmal; Zahara, Alfi Wahyu; Azhari, Faiz (International Journal of Language and Culture, 2025)
This study examines the impact of popular language on the transformation of meaning and social identity in contemporary society, particularly within digital culture and social media. The identified problem is how popular language develops and functions as a social symbol that shapes behavior and social identity in the digital age. This study employs a qualitative approach using a literature review method, with data obtained from various journals, articles, and previous studies on the etymology of popular language and its impacts. The findings show that popular language, such as the terms “selfie,” “hashtag,” and “viral,” not only reflects digital phenomena but also functions to form a more inclusive social identity and introduces new values into society. Additionally, these terms significantly influence shaping social trends and reinforcing existing social norms.